Growth performance, behavior, gene expression, carcass characteristics, stress indicators, and economical parameters of avian 48 broiler chickens raised under three different stocking density - Sakr, Shimaa A.; Abouelnaga, Ahmed F.; Ateya, Ahmed I.; Hashem, Nada M. A.; Wahed, Noha M.; Rehan, Ibrahim F.; Elnagar, Asmaa; Zigo, František; Siedoi, Illia; Kamel, Walied A.; El-Emam, Huda A. (Frontiers in Veterinary Science, 2025)
The current research evaluated the consequence of varying stocking densities on growth performance, carcass features, hematological, welfare, economic parameters, and immune markers of broiler chicks. A total of 324 Avian 48 were haphazardly classified into three different stocking densities. There were 14 birds/m2 in the low stocking density (LSD) group, 18 birds/m2 in the medium stocking density (MSD) group, and 22 in the high stocking density (HSD) group. Compared to the other two groups, the HSD birds’ body weight and daily weight gain were significantly lower (p < 0.05). The LSD group demonstrated a significant increase in productive efficiency (EPEF and EBI) compared to the medium and high SD groups (p < 0.003). The birds from the HSD group exhibited the lowest values for carcass characteristics compared to the low and medium SD groups. At the hematological level, the HSD group exhibited significantly elevated levels of HB, RBCs, heterophils, and lymphocytes compared to the LSD and MSD groups (p < 0.011, p < 0.0001, and p < 0.0001), respectively. Compared to the LSD group, the levels of cortisol, a hallmark of oxidative stress, were considerably greater in the MSD and HSD groups (p < 0.0001). Concerning gene expression, the birds in the LSD group exhibited a significant improvement in growth, intestinal health, and anti-inflammatory genes compared to the MSD and HSD groups. In addition, inflammatory markers were significantly downregulated. The HSD group exhibited the lowest net profit compared to the other groups (p < 0.0001). At the behavioral level, birds in the LSD group demonstrated a significantly shorter TI duration (p < 0.0001) and latency (p < 0.043) in OFT to the first step, lower mobility duration (p < 0.004), and pecking (p < 0.05) compared to other groups. Our study concluded that rearing in LSD up to MSD could be applied without compromising broiler performance.